(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
The paper presents a study of biodiesel application and its ecological impacts. Our study is based on the comparison of exhaust emission composition produced by the combustion of rapeseed oil methyl ester (RME) and conventional diesel fuel (DD) and its blends in a direct injection diesel engine XD2P (YTT). The engine was tested in biofuels laboratory of LUA Motor Vehicle Institute. Fueling the engine with biodiesel and biodiesel/diesel blend reduced oxides of nitrogen by 17.5% (100RME) and by 5.6% (35RME) and carbon monoxide by 49.8% (100RME) and by 45.3% (35RME). Fueling the engine with biodiesel and different biodiesel/diesel blends reduced the absorption coefficient by 33.9% (5RME), by 44.3% (20RME), by 48.3% (35RME) and by 51.2% (100RME) on free acceleration regime. In these tests soot reduced by 28...76.7% at full opened throttle position with 100RME.